Effects of BaSO4 nano-particles on the enhancement of the optical performance of white LEDs - Huu Phuc Dang; Phung Ton That; Dao Huy Tuan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The usage of BaSO4 nanoparticles on WLEDs luminous flux and color uniformity improvements have been analyzed and demonstrated in this manuscript. The mixture of BaSO4 and silicone placed on the yellow phosphor layer benefits the internal light scattering and thus enhances the angular correlated color temperature (CCT) homogeneity. Specifically, the blue-light intensity at large angles tend to increase and results in light intensity discrepancy, which can be corrected with added BaSO4. In addition to this, the BaSO4-silicone composite modifies the refractive index of the air-phosphor layer interface to an appropriate value, and thus, the luminous efficiency increases. The results show that the CCT deviations is reduced by 580 K, from 1000 K to 420 K, within the angle range from -700 to +700 with BaSO4 in the phosphor structure. The increase in luminous flux is also recorded by 2.25%, in comparison with that of the non-BaSO4 traditional structure, at the 120-mA driving current. Hence, integrating BaSO4 nanoparticles into the remote phosphor structure can contributes to the enhancement of both lumen output and CCT uniformity.